Impact of biochar colloids on thallium(I) transport in water-saturated porous media: Effects of pH and ionic strength. (January 2023) - Cao, Yu; Ma, Chengxue; Yao, Jinni; Chen, Wanpeng; Gu, Li; Liu, Hongxia; Liu, Caihong; Xiong, Jiaming; Huangfu, Xiaoliu
Abstract: Understanding the migration behavior of thallium (TI) in subsurface environments is essential for Tl pollution prevention. With the wide production and utilization of biochar, the notable ability of biochar colloids to carry environmental contaminants may make these colloids important for Tl(I) mobility. This study systematically investigated the impact of wood-derived biochar (WB) and corn straw-derived biochar (CB) colloids on Tl(I) transport in water-saturated porous media under different pH (5, 7 and 10) and ionic strengths (ISs) (1, 5 and 50 mM NaNO3 ). WB colloids improved Tl(I) transport under all IS conditions at pH 7 due to the adsorption capacity of biochar and competition for adsorption sites on the sand surface. However, at IS 50 mM, CB colloids slightly impeded Tl(I) mobility due to the straining. In addition, both WB and CB colloids accelerated Tl(I) mobility under all pH conditions at IS 5 mM. At pH 10, the promotion effect was more obvious due to the deprotonation of O-containing functional groups and higher fluidity of biochar colloids. Furthermore, the two-site nonequilibrium model and two-site kinetic attachment/detachment model suitably described the breakthrough curves (BTCs) of Tl(I) and biochar colloids, respectively. The colloid-facilitated solute transport model could also describe Tl(I) transport influenced by biochar colloids reasonably well. This study provides insight into the migration and fate of Tl(I) in the presence of biochar colloids. Graphical abstract: Image 1 Highlights：: Biochar colloids impacted Tl(I) migration through complexation with Tl(I). WB colloids facilitated Tl(I) migration under all experimental conditions. CB colloids slightly impeded Tl(I) migration at high IS. The deprotonation of functional groups accelerated Tl(I) mobility at high pH.